New mutation found to cause hereditary thrombotic thrombocytopenic purpura in a patient presenting with seizures in adulthood - Carolyne Elbaz; Michelle Sholzberg; Hina Hanif; Arnaud Bonnefoy; Katerina Pavenski (Platelets, 2020)
We present a case of hereditary thrombotic thrombocytopenic purpura (hTTP) caused by a previously undescribed mutation in a 36-year-old woman who presented with seizures in the context of a possible infection. Her hematologic manifestations were mild, despite undetectable ADAMTS13 (A Distintegrin and Metalloproteinase with Thrombospondin Motifs 13) activity. Genetic analysis showed a homozygous variant in ADAMTS13 gene which was not previously reported but predicted to be associated with disease. She responded to plasma therapy. Her diagnosis subsequently led to the diagnosis of hTTP in her younger sibling who presented with unexplained strokes a few years earlier.